A Halal Tourism in Indonesia - Case Study in Lombok, West Nusa Tenggara - Nugroho, Dhimas Setyo (Media Wisata, 2024)
The present study aims to conduct implementation of halal tourism in Lombok, as the best halal tourism destination in Indonesia. The topic that will be presented through interactive data analysis until the data is saturated is about Halal tourism institutional, Community empowerment, Community participation, Marketing, Halal tourism investment development and Penalties for violating the provisions of halal certification. A semi-structured interview approach to key informants. The results show that the implementation and development of halal tourism on the island of Lombok is still in its early stages. Indonesia has an organization that guides Islamic economic and financial law for halal tourism fatwas and halal certification. The local government and Indonesian clerical organizations have worked together to achieve halal tourism in Lombok. Efforts to create a halal tourism brand have not materialized due to natural disasters and the COVID-19 pandemic. It is expected that the causal chain frameworks developed in this study will provide a research roadmap for academics as well as insights for the government and the tourism industry in developing a halal tourism model in Indonesia.